The Noradrenergic System in Parkinson’s Disease - Paredes-Rodriguez, Elena; Vegas-Suarez, Sergio; Morera-Herreras, Teresa; De Deurwaerdere, Philippe; Miguelez, Cristina (Frontiers in Pharmacology, 2020)
Nowadays it is well accepted that in Parkinson’s disease (PD), the neurodegenerative process occurs in stages and that damage to other areas precedes the neuronal loss in the substantia nigra pars compacta, which is considered a pathophysiological hallmark of PD. This heterogeneous and progressive neurodegeneration may explain the diverse symptomatology of the disease, including motor and non-motor alterations. In PD, one of the first areas undergoing degeneration is the locus coeruleus (LC). This noradrenergic nucleus provides extensive innervation throughout the brain and plays a fundamental neuromodulator role, participating in stress responses, emotional memory and control of motor, sensory and autonomic functions. Early in the disease, LC neurons suffer modifications that can condition the effectiveness of pharmacological treatments, and importantly, can lead to the appearance of common non-motor symptomatology. The noradrenergic system also exerts anti-inflammatory and neuroprotective effect on the dopaminergic degeneration and noradrenergic damage can consequently condition the progress of the disease. From the pharmacological point of view, it is also important to understand how the noradrenergic system performs in PD, since noradrenergic medication is often used in these patients, and drug interactions can take place when combining them with the gold standard drug therapy in PD, L-DOPA. This review provides an overview about the functional status of the noradrenergic system in PD and its contribution to the efficacy of pharmacological-based treatments. Based on preclinical and clinical publications, a special attention will be dedicated to the most prevalent non-motor symptoms of the disease.